Identifikasi Partisipasi Masyarakat Desa Wisata Alam Endah sebagai Modal Pengembangkan Pariwisata di Ciwidey, Kabupaten Bandung - Hutapea, Rian Bastian; Rahmafitria, Fitri; Nurazizah, Ghoitsa Rohmah; Redo Pratama, Armandha (Jurnal Abdimas Pariwisata, 2024)
The Level of Community Participation in Developing Tourism in Endah Nature Tourism Village, Ciwidey, Bandung Regency Community participation is an essential element in various development and growth processes, including tourism development. Particularly in a tourist village, community participation is an effort to ensure that the community directly benefits from tourism development. In the endeavor of community service, analyzing the level of community participation is an important step to examine the various forms of community participation in developing tourism in Desa Wisata Alam Endah (Alam Endah Tourism Village). This participation mapping utilizes a descriptive method with a qualitative approach. Information and data are collected through field observations and interviews with the local community. Referring to White's theory (1996), the obtained results indicate that the level of community participation in Desa Wisata Alam Endah is at an ideal level, with active participation from the community throughout the planning and implementation stages. Therefore, it can be concluded that Desa Wisata Alam Endah has a relatively strong foundation in terms of community participation.